33 Dying to Know: a pilot to deliver personal development curriculum on death and bereavement in a secondary school in Gateshead. (14th March 2023) - Charles, Max; Orr, Dawn; Waterfield, Kerry
Abstract : Introduction: The aim of the Dying to Know project was to improve young people's engagement with key issues surrounding death, dying and bereavement in order to better equip them to deal with life experiences. The Specialist Palliative Care Team (SPCT) at Gateshead Health NHS Foundation Trust collaborated with Emmanuel College in Gateshead to develop a personal development curriculum on the subject. Methods: Over a 6-month period in 2022, teachers and palliative care professionals delivered lectures and tutorials for 190 young people aged 14–16. Students and teachers were surveyed before and after the programme using free text responses and Likert scales. Results: The post-intervention survey was completed by 189 of the 190 pupils at the end of 2022. Of the 114 free text comments, 49% were positive, including the sessions being informative (43%) recognising the importance of talking about dying (12%) and increasing levels of comfort (4%). 31% of students disliked the title, 10% criticised the emotional response it caused, 10% were not interested in the programme and 5% did not like the lecture format. All teachers thought the programme should be continued. Conclusions: We successfully developed and delivered a teaching programme on death and dying to secondary school pupils. Based on feedback from students and teachers, we plan to revise some content and the name, then expand to other schools. Changing the lectures to video format will improve reproducibility and have less impact on SPCT time. Showing them to 3 different year groups will facilitate development and reinforce learning over time, supported by a drop in 'any questions' session by the SPCT during the same week. The schools will nominate a staff member to lead on this project and be a point of contact for a SPCT link nurse for each secondary school in the borough.